Racial quotas: a study about university student’s and non-university’s social representations - Techio, Elza Maria (2019)
This work aimed at analyzing the positioning of students and non-students about racial quotas in the Brazilian public universities and the justifications for that positioning. We also investigated the levels of prejudice existing among the participants and the relationship between their skin color and their positions about those quotas. The participants were 83 students and 63 non-students. The results showed that non-students perceive themselves as more prejudiced and 74% of the them were favorable to the quotas, being the selfdeclared black those that indicated greater agreement. The lexical analysis showed that students anchor their positions in meritocratic principles, while non-students anchor on egalitarian principles, reflecting the way in which these groups symbolically construct the meaning of racial quotas based on their group memberships.